EndoGame: Gamification Web Platform for Internal Marketing - Junior, Warley; Saraiva, Paline; Malon, Manoel; Randler, Jhon; Oliveira, Lucas; Antonio, Lucas; Oliveira, Arthur; Fernandes, Thiago; Leite, Cristina; Kuribayashi, Hugo (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
Many organizations are still not fully leveraging internal marketing and gamification strategies, often due to a lack of effective tools for implementation. This can result in significant disengagement among employees and a decrease in productivity. Based on this issue, proposed platform aims to act as a support tool for organizations, providing necessary functionalities to effectively implement gamification strategies for internal marketing. It may assist organizations in achieving better results in their goals and objectives.